Linkage map for chromosome-level genome anchoring and genome-wide association study for resistance to Aeromonas hydrophila in Colossoma macropomum - Ariede, Raquel B. [UNESP] (2022)
Tambaqui (Colossoma macropomum) is the most important neotropical fish in freshwater aquaculture in South America. Disease outbreaks caused by the bacterium Aeromonas hydrophila have resulted in significant losses to tambaqui production. Selective breeding using genomic information is a powerful strategy to improve disease resistance in fish species. The first step to incorporating genomic information in breeding programs is determining the number of loci or genes that can affect targeted traits. In this study, we developed a dense linkage map for chromosome-level scaffolding and investigated the genetic architecture of resistance to A. hydrophila in tambaqui in a genome-wide association study (GWAS). The single nucleotide polymorphism (SNP) genotypes from 275 animals belonging to 18 full sib-families were obtained using the novel genotyping platform Axiom 30 K SerraSNP array for tambaqui. The genomic analysis revealed low to moderate heritability values for both resistance trait definitions: h2 = 0.26 (0.10) for test survival and h2 = 0.27 (± 0.10) for time to death. A dense linkage map was developed for tambaqui using the genotype data, resulting in 17,374 SNPs distributed across 27 linkage groups. The length of linkage groups varied from 124 (LG1) to 50 (LG14) cM, with a total integrated map length of 2298.91 cM. The female map was longer than the male map. GWAS analysis identified several putative QTLs associated with A. hydrophila resistance, distributed in six linkage groups. Several candidate genes related to immune response were located close to the putative QTLs, such as irf4a, ripk1l, il20ra, c8a, c8b, ube3c, and ccr9a. This study represents the first application of a 30 K SNP array to build a dense linkage map anchoring 27 megascaffolds (chromosomes) of the genome, and to identify genetic variants associated with A. hydrophila resistance in tambaqui.